Literature Study on the Implementation of Public Administration Ethics by ASN in Palangka Raya City - Deny Saputra, Julius; Alfianus, Alfianus; Pranata, Yoga; Kumalasari, Intan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aimed to analyze the implementation of public administrative ethics by civil servants in Palangka Raya City through a literature-based approach that focused on scholarly sources, national regulatory frameworks, and official institutional documents. A content analysis method was applied to identify the relevance of administrative ethics in the interaction between formal regulations, bureaucratic culture, and individual ethical awareness among civil servants. The findings showed that although a comprehensive normative framework for civil service ethics had been established, its implementation faced significant challenges, including weak internalization of moral values, the persistence of patrimonial culture, and limited effectiveness of integrity-based supervision. These conditions indicated a gap between normative ethics and ethical practices in the field, which negatively affected the quality of public service delivery. The study concluded that strengthening administrative ethics required a paradigm shift from mere regulatory compliance to sustainable public value orientation through ethical leadership and the integration of local cultural values.